2009
DOI: 10.1177/000841740907600303
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Experiences among Children with Disabilities Who Attend Mainstream Australian Schools

Abstract: Occupational therapists need to work collaboratively with educational staff, students, and their peers to create inclusive school settings that facilitate positive friendship experiences for children with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…In children with developmental disabilities, however, friendships and other relationships may possess unusual characteristics and understanding of the term "friend" and may not necessarily be the same as for typically developing peers. Researchers examining children with disabilities have used a variety of methods to infer the existence or non-existence of friendships, often consisting of a direct question as to whether a peer is a friend (e.g., Evans, et al, 1992;Kuo, et al, 2011;Lee, Yoo, & Bak, 2003;Locke, Ishijima, Kasari, & London, 2010) and have often assumed a preexisting friendship when examining features or interactions between the individuals involved in the relationship (Freeman & Kasari, 2002;Matheson, Olsen, & Weisner, 2007;Morrison & Burgman, 2009). Researchers, however, have not typically attempted to determine the extent to which these relationships actually met the criteria of friendship as it has traditionally been defined and the correspondence between nominations of friends and the expected features of friendship.…”
Section: Mutual Liking Enjoyment and Shared Interactions In The Clomentioning
confidence: 99%
“…In children with developmental disabilities, however, friendships and other relationships may possess unusual characteristics and understanding of the term "friend" and may not necessarily be the same as for typically developing peers. Researchers examining children with disabilities have used a variety of methods to infer the existence or non-existence of friendships, often consisting of a direct question as to whether a peer is a friend (e.g., Evans, et al, 1992;Kuo, et al, 2011;Lee, Yoo, & Bak, 2003;Locke, Ishijima, Kasari, & London, 2010) and have often assumed a preexisting friendship when examining features or interactions between the individuals involved in the relationship (Freeman & Kasari, 2002;Matheson, Olsen, & Weisner, 2007;Morrison & Burgman, 2009). Researchers, however, have not typically attempted to determine the extent to which these relationships actually met the criteria of friendship as it has traditionally been defined and the correspondence between nominations of friends and the expected features of friendship.…”
Section: Mutual Liking Enjoyment and Shared Interactions In The Clomentioning
confidence: 99%
“…; Carter et al . ; Morrison & Burgman ; Diez ), while the assistance of classmates, such as to carry books, helps students with and without disabilities to participate more positively in classroom activities and breaks (Eriksson et al . ; De Schauwer et al .…”
Section: Introductionmentioning
confidence: 99%
“…The social environment has been shown to influence participation both positively and negatively depending on the context. Close proximity of adults and negative attitudes of others may affect participation negatively (Richardson 2002;Hemmingsson et al 2003;Carter et al 2008;Morrison & Burgman 2009;Diez 2010), while the assistance of classmates, such as to carry books, helps students with and without disabilities to participate more positively in classroom activities and breaks (Eriksson et al 2007;De Schauwer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Friendship has been addressed in children with developmental disability (Buysse, Goldman, & Skinner, 2002;Freeman & Kasari, 2002;Morrison & Burgman, 2009). For example, Webster and Carter (2010b) examined several specific features of friendship, such as companionship and validation and caring, in the relationships of children with developmental disability and peers in inclusive settings.…”
mentioning
confidence: 99%
“…For example, Webster and Carter (2010b) examined several specific features of friendship, such as companionship and validation and caring, in the relationships of children with developmental disability and peers in inclusive settings. Similarly, Morrison and Burgman (2009) interviewed 10 children with developmental disability to explore their friendship experiences in home, community, and school settings and found that these experiences were extremely varied and included both stories of reciprocal relationships and experiences of social isolation. Nevertheless, there has been a very limited examination of the broader types of relationships, either positive or negative, which children with disability form with peers in inclusive school settings.…”
mentioning
confidence: 99%